Tumor sink effect in 68Ga-PSMA-11 PET: myth or reality? - Gafita, Andrei; Wang, Hui; Robertson, Andrew; Armstrong, Wesley R.; Zaum, Raphael; Weber, Manuel; Yagubbayli, Farid; Kratochwil, Clemens; Grogan, Tristan R.; Nguyen, Kathleen; Navarro, Fernando; Esfandiari, Rouzbeh; et al. (Journal of nuclear medicine, 2022)
Visual Abstract - Download figureOpen in new tabDownload powerpoint - - We aimed to systematically determine the impact of tumor burden on 68Ga-prostate-specific membrane antigen-11 (68Ga-PSMA) PET biodistribution by the use of quantitative measurements. Methods: This international multicenter, retrospective analysis included 406 men with prostate cancer who underwent 68Ga-PSMA PET/CT. Of these, 356 had positive findings and were stratified by quintiles into a very low (quintile 1, ≤25 cm3), low (quintile 2, 25-189 cm3), moderate (quintile 3, 189-532 cm3), high (quintile 4, 532-1,355 cm3), or very high (quintile 5, ≥1,355 cm3) total PSMA-positive tumor volume (PSMA-VOL). PSMA-VOL was obtained by semiautomatic segmentation of total tumor lesions using qPSMA software. Fifty prostate cancer patients with no PSMA-positive lesions (negative scan) served as a control group. Normal organs, which included salivary glands, liver, spleen, and kidneys, were semiautomatically segmented using 68Ga-PSMA PET images, and SUVmean was obtained. Correlations between the SUVmean of normal organs and PSMA-VOL as continuous and categoric variables by quintiles were evaluated. Results: The median PSMA-VOL was 302 cm3 (interquartile range [IQR], 47-1,076 cm3). The median SUVmean of salivary glands, kidneys, liver, and spleen was 10.0 (IQR, 7.7-11.8), 26.0 (IQR, 20.0-33.4), 3.7 (IQR, 3.0-4.7), and 5.3 (IQR, 4.0-7.2), respectively. PSMA-VOL showed a moderate negative correlation with the SUVmean of the salivary glands (r = −0.44, P < 0.001), kidneys (r = −0.34, P < 0.001), and liver (r = −0.30, P < 0.001) and a weak negative correlation with the spleen SUVmean (r = −0.16, P = 0.002). Patients with a very high PSMA-VOL (quintile 5, ≥1,355 cm3) had a significantly lower PSMA uptake in the salivary glands, kidneys, liver, and spleen than did the control group, with an average difference of −38.1%, −40.0%, −43.2%, and −34.9%, respectively (P < 0.001). Conclusion: Tumor sequestration affects 68Ga-PSMA biodistribution in normal organs. Patients with a very high tumor load showed a significantly lower uptake of 68Ga-PSMA in normal organs, confirming a tumor sink effect. As similar effects might occur with PSMA-targeted radioligand therapy, these patients might benefit from increased therapeutic activity without exceeding the radiation dose limit for organs at risk.